![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) `x^2+4-2(x-1)=(x-2)^2`
`<=>x^2+4-2x+2=x^2-4x+4`
`<=>-2x+2=-4x`
`<=>2x=-2`
`<=>x=-1`
.
2) ĐKXĐ: `x \ne \pm 3`
`(x+3)/(x-3)-(x-1)/(x+3)=(x^2+4x+6)/(x^2-9)`
`<=>(x+3)^2-(x-1)(x-3)=x^2+4x+6`
`<=>x^2+6x+9-x^2+4x-3=x^2+4x+6`
`<=>10x+6=x^2+4x+6`
`<=>x^2-6x=0`
`<=>x(x-6)=0`
`<=>x=0;x=6`
.
3) ĐKXĐ: `x \ne \pm 3`
`(3x-3)/(x^2-9) -1/(x-3 )= (x+1)/(x+3)`
`<=>(3x-3)-(x+3)=(x+1)(x-3)`
`<=> 2x-6=x^2-2x-3`
`<=>x^2-4x+3=0`
`<=>x^2-x-3x+3=0`
`<=>x(x-1)-3(x-1)=0`
`<=>(x-3)(x-1)=0`
`<=> x=3;x=1`
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
a: Ta có: \(\left(x-3\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2+3x^2=-33\)
\(\Leftrightarrow x^3-9x^2+27x-27-x^3+27+6x^2+12x+1+3x^2=-33\)
\(\Leftrightarrow39x=-34\)
hay \(x=-\dfrac{34}{39}\)
b: Ta có: \(\left(x-3\right)\left(x^2+3x+9\right)-x\left(x-2\right)\left(x+2\right)=1\)
\(\Leftrightarrow x^3-27-x^3+4x=1\)
\(\Leftrightarrow4x=28\)
hay x=7
c: Ta có: \(\left(x+2\right)\left(x^2-2x+4\right)-x\left(x-3\right)\left(x+3\right)=26\)
\(\Leftrightarrow x^3+8-x^3+9x=26\)
\(\Leftrightarrow x=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3\left(x+3\right)-2x+9\)
\(=3x+9-2x+9\)
\(=x+18\)
đề bài lạ == cứ rút gọn á
\(3\left(x+3\right)-x2+9\)
\(=3x+9-2x+9\)
\(=x+18\)